OPTIMIZATION OF TILT ANGLE FOR FIXED TILT SOLAR PV SYSTEM: CASE STUDY FOR USIM, NILAI, NEGERI SEMBILAN - Ahamad, M. K. F.; Abdulrahim, Khairi bin (Journal of Engineering and Technology (JET), 2025)
This study investigates the optimal tilt angle for fixed-tilt solar photovoltaic (PV) systems and identifies a suitable site for solar farm development at Universiti Sains Islam Malaysia (USIM) in Nilai, Negeri Sembilan, Malaysia. Experimental data were collected from Terco PST2291 solar modules positioned at various tilt angles of 5°, 10°, 20°, 30°, 40°, and 50°, and supplemented with PVsyst software simulations. The results indicate that a 5° tilt angle maximizes energy yield under local climatic conditions. A site suitability analysis was conducted to determine the best location for a solar farm within the USIM campus. Five potential sites were evaluated based on economic viability, energy production potential, accessibility, and land availability. Site 4 emerged as the most suitable option, with the highest energy generation of 9963 MWh/year, offering optimal conditions for solar energy harvesting and infrastructure development. Site 4’s larger area and superior solar irradiance result in the highest energy generation potential. Economic analysis confirms its feasibility, with a competitive Levelized Cost of Electricity (LCOE) and strong Return on Investment (ROI), making it a financially viable choice for sustainable energy production. This article provides valuable insights into optimizing solar PV system design and deployment in Malaysia, supporting USIM’s sustainability goals and serving as a reference for future solar energy projects in similar climatic regions.